2022
DOI: 10.1038/s41525-022-00318-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic effects of propranolol and primidone converge on molecular pathways relevant to essential tremor

Abstract: Essential tremor (ET) is one of the most common movement disorders, affecting nearly 5% of individuals over 65 years old. Despite this, few genetic risk loci for ET have been identified. Recent advances in pharmacogenomics have previously been useful to identify disease related molecular targets. Notably, gene expression has proven to be quite successful for the inference of drug response in cell models. We sought to leverage this approach in the context of ET where many patients are responsive to two drugs: p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…In fact, propranolol ameliorated the overall fitness of poly(GA) and ALS C9orf72 neurons, as demonstrated by the increased levels of the synaptic proteins and the improved survival observed upon treatment. Accordingly, RNAseq experiments have shown that propranolol treatment modifies the expression of genes involved in neuronal survival and axon guidance ( Castonguay et al, 2022 ), which supports the specific effect exerted by this molecule in poly( ) neurons that was highlighted by the blue cluster of our proteomic analysis. These results also revealed that the beta blocker, in line with its lysosomotropic properties ( Müller et al, 2020 ), triggers lysosomal degradation to efficiently reduce the aggregates accumulating within ALS-related neurons without influencing macroautophagy or proteasomal activity.…”
Section: Discussionsupporting
confidence: 71%
“…In fact, propranolol ameliorated the overall fitness of poly(GA) and ALS C9orf72 neurons, as demonstrated by the increased levels of the synaptic proteins and the improved survival observed upon treatment. Accordingly, RNAseq experiments have shown that propranolol treatment modifies the expression of genes involved in neuronal survival and axon guidance ( Castonguay et al, 2022 ), which supports the specific effect exerted by this molecule in poly( ) neurons that was highlighted by the blue cluster of our proteomic analysis. These results also revealed that the beta blocker, in line with its lysosomotropic properties ( Müller et al, 2020 ), triggers lysosomal degradation to efficiently reduce the aggregates accumulating within ALS-related neurons without influencing macroautophagy or proteasomal activity.…”
Section: Discussionsupporting
confidence: 71%
“…Recent studies have investigated additional molecular mechanisms of propranolol in the brain, finding evidence that propranolol can inhibit protein synthesis and induce nitric oxide and hydrogen peroxide secretion in certain brain regions [ 113 , 114 , 115 ]. There is also new evidence that propranolol induces transcriptomic changes in several genes tied to essential tremor etiology [ 116 ]. These studies demonstrate that propranolol may affect complex signaling cascades involving molecular pathways that influence myriad intracellular processes [ 117 , 118 ], supporting the notion that propranolol likely has complex effects on brain biochemistry beyond immediate effects of beta-adrenergic blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Research involving propranolol has identified potential cellular and molecular mechanisms involved in tremor reduction and identifies relevant genetic biomarkers for the drug response in essential tremor (ET). Propranolol has been found to influence the expression of genes previously associated with essential tremor and other movement disorders such as TRAPPC11 ( Castonguay et al, 2022 ). Propranolol also proved to be effective in reducing pain associated with temporomandibular disorders in people with migraine ( Tchivileva et al, 2021 ).…”
Section: Propranolol–an Old Drug With New Propertiesmentioning
confidence: 99%